Islamic Ecological Justice: A Comprehensive Islamic Approach Towards Peatland Sustainability - Titin Apung Atikah; Sri Mujiarti Ulfah; Neny Kurniawati; Yuli Pitriah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Peatlands play a crucial role in maintaining the balance of the global ecosystem and the sustainability of local communities. However, various development policies, such as the One Million Hectare Peatland Development Project (PLG) and the Food Estate program, have demonstrated failure in sustainably managing peatlands, leading to environmental degradation, social conflict, and economic inequality. This article proposes an alternative approach based on Islamic Ecological Justice, integrating sharia principles—such as tawḥīd, khalīfah, mīzān, and maṣlaḥah—into a Khilafah-based peatland governance system. This research employs a qualitative approach through a thematic literature review covering five focuses: peatland ecological characteristics and challenges, national policies and their failures, sensor-based environmental monitoring technology, Islamic ethical principles in natural resource governance, and community-based adaptive cultivation strategies. The findings indicate that technocratic approaches have not been able to address the ecological and social complexities of peatlands. In contrast, the application of monitoring technology developed by researchers, combined with a public funding system through the Baitul Mal (Islamic Baitul Mal), and adaptive cultivation based on Islamic bioeconomics, offers a holistic solution framework. This approach is not only technically and socially relevant but also confirms that Islam provides a paradigm for natural resource governance that is just, preventative, and sustainable.